Thinspiration a study on thin-ideal internalization, body image satisfaction, and self esteem. - Dagangan, Marifel
This study aimed to determine the relationship of thin-idea internalization, body image satisfaction, and self-esteem among pre-adolescents. The research design followed the correlational approach. 70 respondents were chosen through systematic random sampling and composed of preadolescents ranging from 9-12 years olds. Pearson?s R was used to determine the correlation among body image satisfaction, thin-ideal internalization, and self-esteem and Linear Regression Analysis was used to determine whether body image satisfaction and thin-ideal internalization could predict self-esteem. The results of this study only supported one of the four hypotheses proposed. Body image satisfaction was shown to be significantly associated with thin-ideal internalization which indicates that pre-adolescents who are fairly contented with their perceived body image tend to agree and follow the thin-ideals reinforced by media. Meanwhile, findings show that there is the correlation between body image satisfaction and self-esteem levels, which was postulated by hypothesis two showed a negative correlation between self-esteem and body image satisfaction. There was also no correlation between self-esteem levels and thin-ideal internalization, which was assumed by hypothesis three. Finally, the results for regression analysis showed a very low variance of self-esteem from body image satisfaction. This means that preadolescents? body image satisfaction and their internalization of the thin ideal do not determine how they regard themselves.